Measure, use, improve! : data use in out-of-school time - Russell, Christina A.; Newhouse, Corey (Current issues in out-of-school time., 2020)
"Measure, Use, Improve! Data Use in Out-of-School Time shares the experience and wisdom from a broad cross-section of out-of-school time professionals, ranging from internal evaluators, to funders, to researchers, to policy advocates. Key themes of the volume include building support for learning and evaluation within out-of-school time programs, creating and sustaining continuous quality improvement efforts, authentically engaging young people and caregivers in evaluation, and securing funder support for learning and evaluation. This volume will be particularly useful to leadership-level staff in out-of-school time organizations that are thinking about deepening their own learning and evaluation systems, yet aren't sure where to start. Authors share conceptual frameworks that have helped inform their thinking, walk through practical examples of how they use data in out-of-school time, and offer advice to colleagues"--